2017
DOI: 10.22438/jeb/38/5/ms-141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of sugar beet genotypes evaluated by microsatellite DNA markers

Abstract: Aim: Methodology:Results: Interpretation:Identification of diverse sugar beet (Beta vulgaris L.) genotypes is essential for using them as parents in sugar beet improvement programme of India. Hence, genetic variation and diversity of elite sugar beet germplasm collection was analysed using microsatellite markers.Genomic DNA of thirteen genotypes was amplified using 14 microsatellite primers containing dinucleotide to compound repeat motifs. Amplified bands were scored on gel, transformed into a binary characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Simple sequence repeats (SSRs) are repeating patterns ranging from 1 to 6 bp generally present in eukaryotic organisms' genomes [22] and are frequently utilized in plant breeding as marker types. SSR markers are commonly used to assess crop genetic diversity due to their consistency with Mendelian co-dominant inheritance, good stability, reproducibility, convenience, and widespread availability within the genome [10,[23][24][25][26]. Various studies revealed that these markers have also been extensively utilized in the gene flow and genetic analysis of sugar beet populations [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Simple sequence repeats (SSRs) are repeating patterns ranging from 1 to 6 bp generally present in eukaryotic organisms' genomes [22] and are frequently utilized in plant breeding as marker types. SSR markers are commonly used to assess crop genetic diversity due to their consistency with Mendelian co-dominant inheritance, good stability, reproducibility, convenience, and widespread availability within the genome [10,[23][24][25][26]. Various studies revealed that these markers have also been extensively utilized in the gene flow and genetic analysis of sugar beet populations [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…One promising way to increase sugar beet (Beta vulgaris L.) productivity is to create new hybrids featuring the best response to environmental changes that can be adjusted by cultivation technology and genetical resistance to uncontrollable environmental factors at certain ontogenetic stages (Roik, 2010;Srivastava et al, 2017;Pazuki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на то, что опубликован целый ряд работ по применению метода микросателлитного анализа в селекционных программах по сахарной свекле как за рубежом (21)(22)(23)(24)(25)(26), так и в России (27)(28)(29), на сегодняшний день отсутствует удобная технология его использования. Для создания такой технологии, позволяющей получать уникальные и стабильные ДНКпрофили, требуется более подробное изучение геномных микросателлитных профилей на большой выборке верифицированного селекционного материала сахарной свеклы.…”
unclassified